Which technique of positioning and immobilization is better for breast cancer patients in postmastectomy IMRT, single‐pole or double‐pole immobilization?. Issue 1 (3rd December 2018) - Xiang, Qun; Jie, Wuyun; Zhu, KuiKui; Wang, Qiong; Cheng, Jing
Abstract: Purpose: Our purpose was to explore which immobilization is more suitable for clinical practice in postmastectomy intensity modulation radiotherapy, the single‐pole position or the double‐pole position? Methods: Patients treated with postmastectomy intensity modulation radiotherapy were eligible. They were selected randomly for single‐pole position or double‐pole position. Dose–volume histogram (DVH) was used to evaluate plans. After their first radiotherapy, the physicians asked a question about the comfort level of their position. The dosimetric parameters, comfort levels, and reproducibility of the two immobilization techniques were collected and analyzed after all patients had finished the whole radiotherapy. Results: Totally, 94 patients were enrolled. Of these, 54 patients were treated with the single‐pole position, 28 (51.9%)had left‐sided lesions. While 40 patients were treated with the double‐pole position, 20 (50%) had left‐sided lesions. Patients' characteristics in two groups were comparable. The single‐pole and double‐pole immobilizations had similar conformity (0.60 ± 0.05 vs 0.60 ± 0.06, P  = 0.887) and homogeneity index (0.14 ± 0.03 vs 0.13 ± 0.03, P  = 0.407). Compared to single‐pole position, double‐pole position typically increased the mean dose, V 20, and V 30 of heart ( P  < 0.05). Moreover, patients in the single‐pole group felt more comfortable than another group ( P  < 0.05). There was no difference in reproducibility between the two groups ( P  > 0.05). Conclusions: Single‐pole position seems to be more comfortable and can reduce dose coverage to heart. Both devices allow for reproducible setup and acceptable dosimetry.